Influence of Hudson Bay on the carbon dynamics of a Hudson Bay Lowlands coastal site - Kristina K. Delidjakova; Richard L. Bello; Kaz Higuchi; Bipin Pokharel (Arctic Science, 2016)
Eddy covariance (EC) estimates of net ecosystem exchange (NEE) and the surface energy balance were gathered from an elevated peat plateau within the Hudson Bay Lowlands near Churchill, Manitoba, Canada (58°43′46″N, 93°49′57″W) during the growing season of 2007. Data were segregated into onshore and offshore wind regimes to assess the advective influence of the generally cold and moist Hudson Bay air masses compared to generally warm and dry air masses of nonmarine origin. Monthly average NEE ranged from an uptake of 0.2 µmol·m−2·s−1 in September to 5.6 µmol·m−2·s−1 in July. Over the growing season, onshore winds from Hudson Bay contributed to an average 4.2 °C reduction in air temperature and an NEE increase of 27%. When normalized with respect to sunlight receipt, the ratio of gross primary production to photosynthetically active radiation (GPP/PAR) was 26% stronger for offshore regimes than for onshore, while the ratio of ecosystem respiration to PAR (ER/PAR) was 71% stronger for offshore regimes. It was concluded that GPP maintains the same strength for both wind regimes, while ER is significantly stronger for offshore regimes, resulting in reduced NEE capacity during periods when winds originate from inland.